SME Financing in Japan during the Global Financial Crisis: Evidence from Firm Surveys - Ono, Arito; Uesugi, Lichiro (Senate Hall, 2014)
Employing data from a unique firm survey, this article examines small and medium-sized enterprise (SME) financing in Japan during the global financial crisis. The major findings of the article are two-fold. First, in terms of credit availability, loans extended by main banks were the "first line of defense" for most Japanese SMEs to deal with the crisis. In contrast, the role of trade credit provided by firms' main suppliers was relatively limited. The Emergency Credit Guarantees (ECG) program introduced by the government in response to the crisis also helped to increase credit availability. Second, in terms of firms' ex-post performance, loans extended by firms' main bank and loans backed by government policy measures contributed to firms' cost restructuring, but had little impact on their profitability, suggesting a lack of sales growth. A key challenge for policy-makers is to provide incentives for SMEs to adopt effective strategies not only for cost-cutting but also for growth.. JEL classifications: G21, G28, G30, G38 Keywords: SME financing, main bank, trade credit, credit guarantees
Keywords: SME financing|main bank|trade credit|credit guarantees